PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA WARUNG KOPI SPORTIVO SIMPANG MESRA BANDA ACEH SELAMA MASA PANDEMI COVID-19 - Muammar Yogi; Sulaiman Sulaiman (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to examinie the effect of Facilities and Service Quality on Customer Loyalty mediated by Customer Satisfaction at the Sportivo Simpang Mesra coffee shop in Banda Aceh during the Covid-19 pandemic. The sampling method in this study used purposive sampling with a sample of 100 respondents who had criteria to be used as samples and the analytical tool used was Sructural Equation Modeling (SEM). The result of this study indicate that the Facility variable affects Customer Satisfaction, the Service Quality variable affect Customer Satisfaction, and the Service Quality variable affects Customer Loyalty to the customer of the Sportivo Simpang Mesra coffee shop in Banda Aceh. Furthermore, the Facility variable has no effect on Customer Loyalty, and the Customer Satisfaction variable as a mediation has no effect on Customer Loyalty, so there is no mediation effect in this studyThis study aims to examine the effect of facilities and service quality on customer loyalty mediated by customer satisfaction at the Sportivo Simpang Mesra coffee shop in Banda Aceh during the Covid-19 pandemic. The sampling method in this study used purposive sampling with a sample of 100 respondents who had criteria to be used as samples and the analytical tool used was structural equation modeling (SEM). The results of this study indicate that the Facility variable affects Customer Satisfaction, the Service Quality variable affects Customer Satisfaction, and the Service Quality variable affects Customer Loyalty to the customer of the Sportivo Simpang Mesra coffee shop in Banda Aceh. Furthermore, the Facility variable has no effect on Customer Loyalty, and the Customer Satisfaction variable as a mediation has no effect on customer loyalty, so there is no mediation effect in this study.